2017
DOI: 10.3892/mmr.2017.6294
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum polysaccharide exhibits cardioprotection in an experimental model of ischemia-reperfusion damage

Abstract: Cardiovascular diseases are a major cause of mortality and disability worldwide. The present study investigated the cardio-protective effects of polysaccharides extracted from Lycium barbarum (LB), the fruit of which is traditionally used in Chinese medicine. Polysaccharides were characterized using Fourier transform infrared spectroscopy and high‑performance liquid chromatography techniques. The present study demonstrated that LB polysaccharides are composed of glucose and fructose monosaccharides in a molar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…Till recent several years LBPs are given increasing attention in the field and most researches focus on its anti‐oxidative property as a free radical scavenger for immunomodulation and anticancer 14, 15, 16. The studies of LBPs on cardiovascular aspect are only limited to the protective phenomena (no discussion of mechanism) on doxorubicin‐induced cardiotoxicity and ischaemia/reperfusion injury of rat heart 21, 22, 23, 24. In the present study, we used the model of miR‐1 Tg mice and demonstrated that LBPs restored the cardiac function impaired by overexpression of miR‐1, as indicated by increase in EF, CO, ESP, and dp/dt max , as well as decrease in ESV and EDV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Till recent several years LBPs are given increasing attention in the field and most researches focus on its anti‐oxidative property as a free radical scavenger for immunomodulation and anticancer 14, 15, 16. The studies of LBPs on cardiovascular aspect are only limited to the protective phenomena (no discussion of mechanism) on doxorubicin‐induced cardiotoxicity and ischaemia/reperfusion injury of rat heart 21, 22, 23, 24. In the present study, we used the model of miR‐1 Tg mice and demonstrated that LBPs restored the cardiac function impaired by overexpression of miR‐1, as indicated by increase in EF, CO, ESP, and dp/dt max , as well as decrease in ESV and EDV.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] The studies of LBPs on cardiovascular aspect are only limited to the protective phenomena (no discussion of mechanism) on doxorubicin-induced cardiotoxicity and ischaemia/reperfusion injury of rat heart. [21][22][23][24] In the present study, we used the model of HF with complicated pathogenesis is associated with loss of cardiac contractility, abnormalities in Ca 2+ handling and altered phosphorylation states of cardiac contractile regulatory protein. 43,44 Our previous study has elucidated that overexpression of miR-1 repressed potential target proteins CaM and cMLCK, which attenuated the phosphorylation of CaMKII, cMyBP-C and MLC2v, leading to impaired sarcomeric assembly and consequent heart dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There- fore, it is believed that DLST protein is related to the production of ATP in heart tissue, which further affects the energy metabolism of the heart, leading to bradycardia (Keßler et al, 2015). A study showed that Lycium barbarum polysaccharide has a protective effect on the myocardial injury caused by ischemia-reperfusion, and the mechanism is that Lycium barbarum polysaccharide enhances the activity of the Na + /K + -ATPase and inhibits the apoptosis of myocardial cells (Hou et al, 2017). Ascleposide, as a type of cardiac glycoside, inhibits cell proliferation and promotes apoptosis.…”
Section: Discussionmentioning
confidence: 99%